Influence of oxygen flow rate on structural, optical and electrical properties of copper oxide thin films prepared by reactive magnetron sputtering - Thitinai Gaewdang; Ngamnit Wongcharoen (My University, 2017)
In this research, copper oxide thin films were prepared by reactive dc magnetron sputtering method on glass substrates with oxygen flow rate in the range of 1-10 sccm. From XRD patterns, formation of Cu2O cubic structure or CuO monoclinic structure was controlled by adjusting oxygen flow rate. Nanocrystallite size of the as-grown films was observed by AFM. From transmittance spectra, direct energy gap varied between 1.97 and 2.55 eV. Electrical conductivity and Hall effect measurements were performed on the films with van der Pauw configuration. The positive sign of the Hall coefficient confirmed the p-type conductivity in all studied films. Important electrical parameters of films as a function of oxygen flow rate were observed. With low resistivity and high mobility values, the films prepared at oxygen flow rate of 8 sccm are identified as suitable candidates for fabrication as absorber layer in solar cell devices.
Keywords: Copper oxide; Copper-based nanomaterials and applications